Failure and progression to total hip arthroplasty among the treatments for femoral head osteonecrosis: a Bayesian network meta-analysis. Issue 1 (18th May 2021) - Migliorini, Filippo; Maffulli, Nicola; Baroncini, Alice; Eschweiler, Jörg; Tingart, Markus; Betsch, Marcel
Abstract: Introduction: Osteonecrosis of the femoral head (ONFH) often leads to secondary osteoarthritis and total hip arthroplasty. Source of data: Recent published literatures. Areas of agreement: There has been increasing focus on the early intervention in ONFH patients to preserve the native hip articulation, reduce pain and improve function. Areas of controversy: Efficacy of surgical strategies for ONFH is debated. Several clinical studies showed controversial results, and the best treatment has not yet been clarified. Growing points: To provide an overview over current treatment options for ONFH compares their failure rates and conversion to total hip arthroplasty (THA) rates. Areas timely for developing research: Core decompression (CD) augmented with autologous bone grafting plus the implantation of bone marrow concentrate can decrease the rate of failure and progression to THA rates compared to CD alone.